Evaluación de la fiabilidad en el sistema web de agendamiento de citas médicas del Hospital General Universitario Andino de la Provincia de Chimborazo - Rivera Guaraca, Mauricio Ismael (2021)
In this research, a web system for scheduling medical appointments developed for the Hospital General Universitario Andino de Chimborazo, to streamline the medical care process. It done based on the requirements established by the institution, using SCRUM agile development methodologies for the design, coding and testing of the software product, obtaining as a result a web application with the modules of: scheduling medical appointments, module of the hospital staff management, patient module and hospital procedures module, this system developed with the React Native framework, the GraphQL query language and the non-relational database engine MongoDB.Through the methodology of evaluation of systems on the web Web-QEM, the evaluation of the reliability criterion in the web application carried out, for this purpose the ISO / IEC 25000 standard analyzed, which provides the sub-criteria of maturity, availability, tolerance to failures, recoverability and their metrics failure elimination, test coverage, mean time between failures, service time, downtime, failure prevention, redundancy, and recovery time. To carry out this process, the Apache JMeter simulation tool used to send requests to the server to check the performance of the application under certain conditions and periods of time, resulting in the percentage of 97.5% of external quality of the software product in the reliability criterion and a remaining 2.5% that used for the improvements of the web application.